Comparison of innovative banking market models and new opportunities for sustainable development between Kyrgyzstan and China under the wave of digital finance - Wang, Xiaojiao; Abdykadyrov, Kalybek Zh. (Edelweiss Applied Science and Technology, 2025)
Against the backdrop of the rapid development of digital finance, the banking industries of the Kyrgyz Republic and China face differentiated challenges: Kyrgyzstan is constrained by weak digital infrastructure, an outdated regulatory framework, and low coverage of traditional banking services, while China needs to deal with issues such as saturated market competition, data security risks, and cross-border payment barriers. Through multi-dimensional comparative analysis, this study first collects annual reports of the central banks of the two countries and World Bank data from 2018 to 2023, and quantitatively evaluates core indicators such as mobile payment penetration rates and digital credit scales; secondly, it selects typical institutional cases to deconstruct product innovation models; finally, it uses the SWOT model combined with policy text analysis to find that Kyrgyzstan has reduced the access cost of micro-merchants from US$138 in 2018 to US$36 in 2023 by introducing a QR code payment system, and the cross-border remittance fee has continued to drop from 8.0% in Q1 2018 to 2.3% in Q4 2023, providing a reference for the sustainable development of digital finance along the "Belt and Road".